Pathogenic analysis of Vibrio alginolyticus infection in a mouse model - Liu, Xiao-Fei; Zhang, Helin; Liu, Xingshan; Gong, Yanwen; Chen, Yingjian; Cao, Yuan; Hu, Chengjin (Folia microbiologica, 2014)
Vibrio alginolyticus is a Gram-negative halophilic bacterium and has been recognized as an opportunistic pathogen to both humans and marine animals. So far, most studies have been focused on marine animals and few reports have been aimed at mammals, including human. In this study, we first established a mouse model to understand the pathogenic mechanism of V. alginolyticus infection. After infection via intraperitoneal injection, hematological and liver function indicators were evaluated and serum interleukin (IL)-1β and IL-6 expression were detected by ELISA. Furthermore, we compared the virulence of two V. alginolyticus strains, ATCC17749T and E0666. The results demonstrated that V. alginolyticus infection causes robust lung and liver damage and induces changes in IL-1β, IL-6, hematological, and liver indicators. In addition, the ATCC17749T strain appeared to be more virulent than the E0666 strain. Better understanding of the pathogenic mechanism of V. alginolyticus infection should guide effective prevention and therapy for V. alginolyticus infection.
Keywords: Liver; jaterní testy; játra; Mice, Inbred BALB C; Vibrio alginolyticus; histocytochemie; Lung; cytokiny; virulence; Disease Models, Animal; Mice; Histocytochemistry; Cytokines; Blood Chemical Analysis; Enzymes; biochemická analýza krve; modely nemocí na zvířatech; ženské pohlaví; Microscopy; zvířata; plíce; Virulence; myši inbrední BALB C; myši; Vibrio Infections; enzymy; Female; Liver Function Tests; mikroskopie; infekce bakteriemi rodu Vibrio; Animals